The Value Relevance of Accounting Information and Its Impact on Market Vulnerability: A Study of Listed Manufacturing Companies in Sri Lanka - Nimalathasan, B. (My University, 2013)
This study examines the impact of value relevance of accounting information on market vulnerability of the listed manufacturing companies in Colombo stock exchange (CSE). Using one of accounting based measure of market vulnerability which is measured by market price per share. The sample of this study composed of twelve companies listed in the CSE and period of 5 five years from 2009 to 2013. The required data and information for the study were gathered from published annual reports, fact book, and website of listed companies in CSE from 2009 to 2013. Descriptive and inferential statistics were used for this purpose for the study. The results revealed that earning per share (EPS) and net assets value per share (NAVPS) significantly impact on market vulnerability. Further EPS and NAVPS are significantly correlated with market vulnerability. Outcome of the study would be beneficial to the practitioners, academicians, policy makers and others.
Keywords: Value Relevance of Accounting Information; Market Vulnerability; Colombo Stock Exchange